Role of competition policy for development in globalizing world markets (UN GenevaCH)
Presents a summary of the proceedings of the seminar. Includes substantive contributions on topics such as globalizarion, competition and development; the role of business and consumers in promoting competitive markets supportive of sustainable development; the role of competion policy in providing a more equitable playing field for development in globalizing markets; and, trilateral networks of government, business and civil society: the role of international organizations in global public policy.
Keywords: COMPETITION POLICY